Model, Taxonomy and Methodology for Research Employing Electroencephalography-based Brain-Computer Interface Games - Mendes, Gabriel Alves Vasiljevic; Miranda, Leonardo Cunha de (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2023: Anais do XXXVI Concurso de Teses e DissertaçõesDO - 10.5753/ctd.2023.229959, 2023)
The thesis summarized in this work presents a model for representing EEG-based BCI games, a taxonomy for classifying and comparing studies of the field, and a methodology for conducting scientific studies using those games. The model is intended to describe and develop new EEG games by instantiating its components. The CoDIS taxonomy considers four aspects of such games: concept, design, implementation and study, each with different dimensions to represent various of their characteristics. Based on the model and the taxonomy, the PIERSE methodology was developed for the planning, implementation, execution and reporting of scientific experiments using those games. The contributions of the thesis are detailed in various dimensions in this manuscript.